Modeling the Influence of Relationship Marketing, Green Marketing and Innovative Marketing on the Business Performance of Small, Medium and Micro Enterprises (SMMES) - E T, Maziriri; E, Chinomona (Journal of Economics and Behavioral Studies, 2016)
Small, Medium and Micro Enterprises (SMMEs) are considered as economic engines for many countries. In South Africa, the Small, Micro and Medium Enterprises (SMMEs) sector has been acknowledged as the driving force to foster economic growth and job creations. This paper aimed at examining how relationship marketing, green marketing and innovative marketing influence the business performance of Small, Medium and Micro Enterprises (SMMEs) in Southern Gauteng, South Africa. The study utilized a quantitative research paradigm. A structured questionnaire consisting of validated scales for relationship marketing, green marketing, innovative marketing and business performance was administered to a sample of 231 SMMEs managerial employees in the Southern Gauteng region of South Africa. Smart PLS was used to analyze the data and the results indicated that there are positive relationships between the posited research variables. Implications of the findings are discussed and limitations and future research directions are alluded to.